Towards understanding mobile messaging ecologies : an exploration of the meanings young people attach to instant messaging channels - Scholtz, Katharina (Centre for Film and Media Studies, 2015)
Mobile communications have added an ever present layer to our personal communication through which social dynamics can be reconstructed. In youth culture specifically, instant messaging allows young people to achieve limited autonomy, explore peer groups and an evolving sense of self. This dissertation explores a model for understanding how instant messaging facilitates this. Theories of media ecologies provide useful ways of explaining media environments. Nonetheless ecologies are usually conceptualised in relation to mass media rather than networked media and tend to assume that ecologies are situated in a particular physical space. The theory is nonetheless useful in understanding the everyday experience of young people using media. By extending media ecology theory to account for the personal communicative ecologies of instant messaging, this study extends the notion of ecology to account for a sense of digital social space outside the constructs of physical space. Through taking an interactional epistemological stance, qualitative research was conducted. Two focus groups were conducted to explore how instant messaging channels meet the needs of a group of young people from middle class contexts in Cape Town. The resultant discussions are applied to the framework of a 'layered' communicative ecology, taking technology, social and discursive layers into account and establishing the centrality of social space within a new and expanded model of networked messaging ecologies. The central aim of this research is to explore how relevant the application of media ecologies would be to an exploration of digital spaces of communication and practice.